Comparison of the effects of a balanced crystalloid‐based and a saline‐based tetrastarch solution on canine whole blood coagulation and platelet function. Issue 1 (7th December 2016) - Reuteler, Annina; Axiak‐Flammer, Shannon; Howard, Judith; Adamik, Katja‐Nicole
Abstract: Objective: To evaluate the effects of a 6% hydroxyethyl starch (130/0.42) solution in either a buffered, electrolyte‐balanced (HES‐BAL), or a saline (HES‐SAL) carrier solution on canine platelet function and whole blood coagulation. Design: Prospective, randomized study. Setting: University teaching hospital. Animals: Thirty‐seven client‐owned dogs undergoing general anesthesia for arthroscopy or imaging studies. Interventions: Dogs received a 15 mL/kg intravenous bolus of HES‐SAL ( n = 13), HES‐BAL ( n = 14), or a modified Ringer's solution ( n = 10) over 30–40 minutes. Coagulation was analyzed using a Platelet Function Analyzer‐100 (closure time [CtPFA ]), and whole blood thromboelastometry (ROTEM) with extrinsically (ex‐tem and fib‐tem) and intrinsically (in‐tem) activated assays, which assessed clotting time (CT), clot formation time (CFT), maximal clot firmness (MCF), and lysis index (LI). Coagulation samples were assayed prior to fluid administration (T0), and 5 minutes (T1), and 3 hours (T2) following fluid bolus administration, respectively. Results: Both HES solutions resulted in impaired platelet function as indicated by a significant prolongation of CtPFA at T1 as compared to T0, but which resolved by T2. An IV bolus of Ringer's solution did not alter platelet function. In both HES groups, whole blood coagulation was significantly impaired at T1 as indicated by a significant increase in in‐tem CFT, and a significant decrease in ex‐tem, in‐tem, and fib‐tem MCF compared to T0. Furthermore, a significant increase in ex‐tem CFT at T1 compared to T0 was found in the HES‐SAL group. With the exception of in‐tem MCF after HES‐BAL, these effects were not present at T2. No significant differences were found in CtPFA or any ROTEM variable at any time point between HES‐SAL and HES‐BAL. Conclusion: Administration of a single bolus of 15 mL/kg 6% HES 130/0.42 results in significant but short‐lived impairment of canine platelet function and whole blood coagulation, regardless of carrier solution.